Innovative Approaches To The Study Of The Teachings Of Eastern Thinkers: Foreign Experience And National Opportunities (Texas Journal of Multidisciplinary Studies, 2025)
This article analyzes the legal doctrines of Eastern thinkers from a jurisprudential perspective. Based on foreign experience in Islamic law research, it offers innovative approaches for integrating the ideas of al-Farabi, Ibn Sina, al-Biruni, and others into contemporary legal scholarship.